Dot-blot immunoassay for detection of tomato chlorosis virus and reaction of potato genotypes to virus infection - Pinto, Luiz R. (2021)
Tomato chlorosis virus (ToCV) is a whitefly-transmitted crinivirus that causes yield losses, mainly in tomato (Solanum lycopersicum) and potato (S. tuberosum) crops. In this work, a polyclonal antiserum for detecting the virus using a dot-blot immunoassay was developed and the responses of crinivirus-infected potato genotypes were evaluated. The virus was purified using infected tomato leaves and the antiserum was obtained by intramuscular injection of purified viral preparations in rabbit. Tomato and potato tissue samples were used to validate the polyclonal antiserum for detection of ToCV, previously analyzed by RT-PCR. A total of 81 tomato and potato samples were analyzed by RT-PCR and dot-blot immunoassay (DBIA). All samples were positive in RT-PCR, but three of them did not react in DBIA, showing of 96.3% efficiency compared with that in RT-PCR. All potato genotypes inoculated with ToCV by Bemisia tabaci MEAM1 were susceptible to infection. Potato plants of cv. Camila infected by ToCV showed the lowest virus titer and were asymptomatic.